On the maximum of stochastic Gaussian field - Lapinskas, R. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Лапинскас. О максимуме однородного нормального поляR. Lapinskas. Apie homogeninio normalinio lauko maksimumą